Assessment of the Phytochemicals and Antioxidant Activity of Baccaurea bracteata Müll.Arg. and Macaranga lowii King ex Hook.f. from East Kalimantan - Dinda; Suwandari, Suhartini; Kurnia, Irmayanti Tri; Hasan, Muhammad Iqbal; Artama, Riro Iraga; Phontree, Kiettipum; Ramadhan, Rico (Universitas Airlangga, 2023)
This study investigated the total phenolic content and antioxidant activity of Baccaurea bracteata Müll.Arg. and Macaranga lowii King ex Hook.f. from East Kalimantan. The leaves of these plant extracts were evaluated for their total phenolic content (TPC) and antioxidant activity, utilizing the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay. The findings indicated that Baccaurea bracteata Müll.Arg. demonstrated superior antioxidant activity with a percent inhibition (PI) value of 68.31 ± 0.11%. This research highlights Baccaurea bracteata Müll.Arg. as a promising source of natural antioxidants, characterized by high total phenolic content of 14.76 ± 1.98 mgGAE/g.